Concentración espacial de capital humano calificado y desigualdad regional de ingresos en el periodo 2003 al 2012. - Cueva Masache, Karla Anabel (2014)
The main objective of this research is based on examining the effect of the concentration of skilled human capital on regional income disparity from 2003 to 2012 by using data from the National Survey on Employment, Unemployment and Underemployment, of the Instituto Nacional de Estadísticas y Censos (National Institute Statistics and Census Bureau), and under the theoretical approach to Spatial Labor Sorting, which suggests that the heterogeneous distribution of human capital on the space is able to explain a significant part of total inequality. In order to get this objetive, a hierarchical linear model of two levels was used. The first level contains the individuals and their individual characteristics, and the second level contains the regions. The results show that skilled human capital is not randomly distributed in the regions, and this significantly affects income inequality. In this sense, the need arise to propose policies of individual and spatial equity, in order to contribute to the reduction of the spatial concentration of skilled human capital in Ecuador.